Taylor Swift's Personal Branding Analysis : From Reputation and Rebranding - Intan Fatona Maharani Putri (Journal Research of Social Science, Economics, and Management, 2025)
The impact of personal branding can be seen when individuals market their self-worth to stand out among competitors, especially through social media as a tool to build a strong image. One public figure who exemplifies effective personal branding is Taylor Swift, a globally influential musician. Known as both a songwriter and singer, as of 2025 she has released twelve albums, each representing a unique era and rebranding concept. Swift consistently reinvents herself by shifting music genres—from country and pop to goth punk and indie folk—while also transforming her visual identity to match each album’s theme. Her lyrical storytelling deeply connects with audiences, evoking strong emotional responses. Moreover, Swift effectively utilizes her social media platforms to strengthen her professional reputation and engage directly with fans. Her Instagram account, for instance, maintains an impressive engagement rate of 2.93%, reflecting a strong and positive audience connection. She also leverages User Generated Content (UGC) strategies, such as initiating dance challenges, to enhance interaction and fan participation. This research applies the Criteria for Effective Authentic Personal Branding by Hubert K. Rampersad and the 3C Model (Credibility, Consistency, Clarity) developed by Avinash Pawar. The findings reveal several dominant elements of Taylor Swift’s personal branding—namely consistency, authority, relevance, goodwill, and performance. Through her strategic self-presentation and creative evolution, Taylor Swift successfully showcases her authenticity and musical excellence, reinforcing her unique identity and long-term influence in the global music industry.